PAPAN KANTONG DAN EFEKTIFITAS PENGGUNAANNYA DALAM PEMBELAJARAN INSYA’ PADA PONDOK PESANTREN MODERN BABUN NAJAH ULEE KARENG BANDA ACEH - Safriana, Safriana; Suhaimi, Suhaimi; Maimunah, Maimunah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2019)
A board bag and the effectiveness of its use in learning writing (experiment research at babun najah islamic boarding school ulee Kareng Banda Aceh). The reasons that motivate researchers to write research, that second grade students MTs, their difficulty in making up the correct use of the Arabic language, because the school does not use the correct media in learning writing. The purpose of this study was to determine the effectiveness of the use of board bags that enhance the ability of students in learning writing. And the research methods used by the researchers is a research experiment. And the researchers collected data using a pre-test, post-test and direct observation. As for the population in this study were all students Babun Najahand researchers select students in grade II (2) as the control class and II (1) as a experiment class the number of 36 students. The results obtained by researchers is the use of board bags are effective in improving students 'ability in learning writing. And it can be seen that t-test is greater than t-table.